Microstructural characterisation and mechanical properties of Ti-5Al-5V-5Mo-3Cr built by wire and arc additive manufacture - Caballero, Armando; Davis, Alec E.; Kennedy, Jacob R.; Fellowes, Jonathan W.; Garner, Alistair; Williams, Stewart; Prangnell, Philip B. (Taylor and Francis, 2022)
The as-deposited microstructure and mechanical properties of the near-β titanium alloy Ti-5Al-5V-5Mo-3Cr (Ti-5553) produced by wire-arc additive manufacture (WAAM) were investigated, to understand its microstructural evolution under WAAM deposition conditions and to establish correlations between the microstructure features formed and the thermal cycles experienced during deposition. The ‘as-deposited’ Ti-5553 WAAM material exhibited higher tensile strengths than other as-deposited additively manufactured Ti-5553 deposits previously reported in the literature, but had significant anisotropy in elongation, as a consequence of the coarse and columnar β-grain structure that formed on solidification, which exhibited a strong {001}β⟨001⟩β cube texture. The multiple reheating cycles, inherent to the WAAM process, were recorded using a novel ‘harpoon’ thermocouple technique, and the α precipitation evolution was related to the thermal history. Electron probe microanalysis chemical maps revealed significant solute microsegregation during solidification, which influenced the subsequent precipitation due to its effect on the local β-phase stability. As each layer experienced more reheating cycles, the microstructure evolution could be ‘time resolved’ and the α laths were found to precipitate in a specific sequence of nucleation sites, starting at the β-grain boundaries and then inter-dendritically, where there was lower matrix β stability. However, after the reheating peak temperature was insufficiently high to have any further effect, the microstructure consisted of a relatively uniform distribution of α laths.
Keywords: Additive manufacture; titanium; phase transformation; texture